THE SIMILARITY OF MOTIVES IN TURKISH FOLK EPICS - Abduvalitov Ergash Buranevich (Modern American Journals, 2025)
Turkic folk epics represent a rich cultural and literary heritage shared by many Turkic-speaking peoples. Despite geographical dispersion and historical differences, these epics demonstrate striking similarities in motifs, themes, character types, and narrative structures. This article explores the common motifs found in major Turkic epics such as Alpamysh, Manas, Dede Korkut, Koroghlu, and Edige. The study analyzes heroic birth, initiation, struggle between good and evil, loyalty, exile and return, and supernatural assistance as recurring epic motifs. By examining these shared elements, the article highlights the unity of Turkic worldview, values, and mythological consciousness preserved through oral tradition.